Efficacy of Keji Beling Leaf Extract Gel (Sericocly Crispi Folium) as an Anti-Ulcer Agent in Alloxan-Induced Diabetic Rat Models: A Histological and Inflammatory Mediator Study - Grace Angel Natalia br tarigan; Muhammad Yunus; Nerly Juli pranita simanjuntak (Jurnal FARMASIMED (JFM), 2026)
Background: Diabetes mellitus is a chronic disease that can cause complications in the form of diabetic ulcers, which are wounds that are difficult to heal due to high blood glucose levels and prolonged inflammation. One herbal plant with potential wound-healing properties is keji beling leaf (Sericocly Crispi Folium), as it contains flavonoids, alkaloids, saponins, and antibacterial compounds. Objective: This study aimed to determine the effect of keji beling leaf extract gel on burn wound healing in alloxan-induced diabetic rats. Methods: This was an experimental study using 30 white rats divided into six groups: normal control, negative control (gel base), positive control (bioplasenton gel), and treatment groups receiving keji beling leaf extract gel at concentrations of 5%, 10%, and 15%. Results : Diabetes was induced using alloxan at a dose of 120 mg/kg body weight. Burn wounds were created on the dorsal area of the rats, followed by treatment for 14 days. Wound healing was evaluated by measuring wound diameter and through histopathological examination of skin tissue. Results and Conclusion: The results showed that keji beling leaf extract gel accelerated wound healing in diabetic rats compared to the negative control. The 15% concentration produced the best outcomes, indicated by the greatest reduction in wound diameter and improved histopathological features, including better re-epithelialization, increased collagen deposition, and reduced inflammation.